Research on Technical Framework of Intelligent Maintenance & Supportfor Heavy-haul Railway - ZHANG Bin; LI Fei; WANG Duo; LYU Gexing; WANG Dalong (Kongzhi Yu Xinxi Jishu)
In recent years, with the emergence and popularization of a series of new intelligent technologies such as cloud computing, big data, IoT, mobile internet and artificial intelligence, how to use resources comprehensively and efficiently to realize comprehensive perception, ubiquitous interconnection, fusion processing, active learning and scientific decision-making of information among railway heavy-haul trains, mobile equipment, fixed infrastructure and internal and external environments, to provide guarantee for the safe and stable operation of heavy haul combined trains on the railway, becomes an important topic at present. This article analyzes the current status of locomotive operation and maintenance of heavy-haul railway, designs an intelligent maintenance and support system for railway based on the six sectors of smart perception, smart diagnosis, smart detection, smart evaluation, smart maintenance and smart security. It analyzes and looks forward to the key breakthrough technologies such as "multi-sensor fusion based on vehicle internet of things" and "fault diagnosis based on shallow knowledge and deep knowledge model" in the transformation to "intelligent service" and puts forward some ideas for the intelligent construction of smart railway series in the future.